Evaluation of the physical characteristics and motoric test results of (male) university students - Sonal, Cetin Erdem; Toksoz, Ilhan; Bilen, Omer (ELSEVIER SCIENCE BV, 2014)
This study was performed with the purpose of assessing physical characteristics and motoric test results of the male students who are attending to university between the ages of 19 and 21 (sedanter n=40 and athlete n=40). A significant difference was not found between the two groups when the values such as Biological age, height, the rate of body-fluid, muscle mass, metabolism speed, and physical activity status were observed each time (p > 0.05). However, a significant difference was detected against the sedentary group as compared to the athletes' group in terms of the Body weight, bone mass, the internal organ fat ratio, body fat rate, 30m sprint and vertical jump rates (p <0.05). Consequently, this study has shown that the lipogenesis in sedentary group restricts physical activities and affects the physical fitness negatively. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: university students; physical characteristics; body fat rate; LEAN BODY-WEIGHT; DENSITY; Education & Educational Research